Functional divergence of diacylglycerol acyltransferases in the unicellular green alga Haematococcus pluvialis. (1st October 2020) - Ma, Haiyan; Wu, Xiaoying; Wei, Ziwang; Zhao, Liang; Li, Zhongze; Liang, Qing; Zheng, Jie; Wang, Yu; Li, Yanhua; Huang, Linfei; Hu, Qiang; Han, Danxiang
Abstract: Acyl-CoA:diacylglycerol acyltransferase (DGAT) catalyzes the final committed step in triacylglycerol biosynthesis in eukaryotes. In microalgae, the copy number of DGAT genes is extraordinarily expanded, yet the functions of many DGATs remain largely unknown. This study revealed that microalgal DGAT can function as a lysophosphatidic acyltransferase (LPAAT) both in vitro and in vivo while losing its original function as DGAT. Among the five DGAT-encoding genes identified and cloned from the green microalga Haematococcus pluvialis, four encoded HpDGATs that showed triacylglycerol synthase activities in yeast functional complementation analyses; the exception was one of the type II DGAT encoding genes, HpDGTT2 . The hydrophobic recombinant HpDGTT2 protein was purified in soluble form and was found to function as a LPAAT via enzymatic assay. Introducing this gene into the green microalga Chlamydomonas reinhardtii led to retarded cellular growth, enlarged cell size, and enhanced triacylglycerol accumulation, identical to the phenotypes of transgenic strains overexpressing CrLPAAT. This study provides a framework for dissecting uncharacterized DGATs, and could pave the way to decrypting the structure–function relationship of this large group of enzymes that are critical to lipid biosynthesis. Abstract : One copy of acyl-CoA:diacylglycerol acyltransferase (DGAT) from microalgae can function as a lysophosphatidic acyltransferase both in vitro and in vivo while losing its original function as DGAT.